Communicating identity among Malaysian students - Koleth, Rebecca John (2011)
This study explored communicating identity among Malaysian students in Universiti Putra Malaysia through various communication forms, as proposed by Mary J. Collier. The communication forms for this study included language, clothing and personal experiences. The study also incorporated cultural problems of ethnocentrism, discrimination, prejudice and bias and coping strategies of cultural relativity, cultural determinism, communication improvement strategies and awareness. Experiences in life shape the communicating of identity. Without knowing these experiences, one may make generalizations and draw inappropriate conclusions leading to a communication breakdown where a person‟s identity is wrongly perceived. This would be a barrier in understanding the world as a whole. The general objective was to determine the identification among Malaysian students in UPM and cultural problems in identification. The specific objectives were: 1) To determine how forms of communication (language, clothing and personal experiences) are incorporated into the identification process. 2) To determine the cultural problems encountered. 3) To determine how students cope with cultural problems in identification. This study was conducted using the phenomenological approach consisting of 15 in-depth interviews and one by e-mail. Location of the study was UPM itself and the setting was one-to-one and informal. Each interview took around 15 to 53 minutes and questions were mostly open-ended. Subjects comprised of Malays, Chinese and Indians, both male and female between the ages of 18 to 50 years. Purposive sampling was used and interviews were audio taped, transcribed verbatim and e-mailed to respondents for approval. The data was sorted using bracketing, coding and categorization and underwent phenomenological analysis. This involved horizontalization of meanings, clustering of themes, textural description, structural description and essential description. The theory was the Cultural Identity Theory by Collier. Findings showed that students immediately mentioned their names when communicating identity and their age too. These revealed an increasingly personalized and individualized identity. It was found that race was not a popular topic and students preferred a juxtaposition of national and ethnic labels. The overall language preference was Malay and the preferred clothing was “casual attire” where traditional clothes were worn only on occasion. In conclusion, students were rather nationalistic in their outlook. Although students supported „one voice, one country‟, there was a definite movement towards a personalized identity. The „one voice, one country‟ mindset may be idealistic in one sense. It would be easier to create a deeper sense of unity if one is aware of one‟s differences but not to lose sight of one‟s identity in the process. The study supported the cultural identity theory which indicated tolerance, change and better understanding between races which the theory also suggested. The contribution of the study was that it would reduce disparity among different cultures while increase the sense of belonging among similar cultures. It would equip one with the intercultural skills to settle and reach agreements in controversial cultural issues.